2D/3D perovskite hybrids as moisture-tolerant and efficient light absorbers for solar cells. Issue 43 (20th September 2016) - Ma, Chaoyan; Leng, Chongqian; Ji, Yixiong; Wei, Xingzhan; Sun, Kuan; Tang, Linlong; Yang, Jun; Luo, Wei; Li, Chaolong; Deng, Yunsheng; Feng, Shuanglong; Shen, Jun; et al.
Abstract : 2D/3D perovskite hybrids achieved significantly improved moisture stability and analogical device performances as compared with homogeneous 3D perovskites. Abstract : The lifetime and power conversion efficiency are the key issues for the commercialization of perovskite solar cells (PSCs). In this paper, the development of 2D/3D perovskite hybrids (CA2 PbI4 /MAPbI x Cl3− x ) was firstly demonstrated to be a reliable method to combine their advantages, and provided a new concept for achieving both stable and efficient PSCs through the hybridization of perovskites. 2D/3D perovskite hybrids afforded significantly-improved moisture stability of films and devices without encapsulation in a high humidity of 63 ± 5%, as compared with the 3D perovskite (MAPbI x Cl3− x ). The 2D/3D perovskite-hybrid film did not undergo any degradation after 40 days, while the 3D perovskite decomposed completely under the same conditions after 8 days. The 2D/3D perovskite-hybrid device maintained 54% of the original efficiency after 220 hours, whereas the 3D perovskite device lost all the efficiency within only 50 hours. Moreover, the 2D/3D perovskite hybrid achieved comparable device performances (PCE: 13.86%) to the 3D perovskite (PCE: 13.12%) after the optimization of device fabrication conditions.